Development of innovative nano-satellites with new generation technologies - Menezes, Ajit Denis (Nanyang Technological University, 2020)
Today’s satellite technology although having major focus on CubeSat technology, is far from optimized in terms of power, weight, structure and overall performance. This Master’s thesis aims to look at designing, developing and qualifying a 3D printed 1U CubeSat structure that can be successfully launched from the International Space Station (ISS). Majority of the structure is designed in such a way that it can be 3D printed using the space qualified polymer ULTEM 9085, with minimal use of support material. It is also designed for easy assembly and disassembly. In addition, the structure is optimized and customized to meet the launcher requirements. The ULTEM structure consists of 6 frames where the side faces have provisions for mounting the solar panels and the top surface has the provision for mounting the antenna. This report also discusses the various mission requirements and non-structural components for the CubeSat. So far, two successful comprehensive design attempts are included and discussed. The testing is first done using ABAQUS to find some measure of the distortions and stresses that can be experienced by the CubeSat structure. The vibrational models show that the extent of displacements and stress is low. Next, further testing carried out on real models utilised a rigid base mounted on two different vibration exciters of different sizes. The models are tested based on performance parameters provided by an established launch agency and analysed under a microscope to check for any cracks or major degradation. The ULTEM is also tested for outgassing properties to ensure it is acceptable for Space applications. The results show that the developed structures can survive the high stresses experienced during the launch phase, and display negligible outgassing. For the Space operation segment, a payload is developed that can measure the temperature of the ULTEM panels and their response to every thermal cycle in Space. The electronic stack is also made up of GomSpace panels that can provide telemetry data and an antenna to transmit data from the payload to the Ground Station. They also manage power with the battery and solar panels. The combination of the payload, electronic stack and tested hybrid CubeSat structure provide a complete mission in terms of operability and research data gained.